Design & development of smart mobility displays for road safety enhancement - Yap, Cai Yong (2017)
This paper aims to enhance safety on the road through wireless communication technology. Its purpose is to broadcast and receive safety alert messages when any safety related actions were made by a driver. This form of wireless communication technology for vehicles is also known as vehicle to vehicle or vehicle to others communications technology. The current safety on the road is primarily based on the driver’s visual observation. As a result, accidents are prone to occur, as drivers and other road users might not be fully aware of their surroundings all the time. This project focus the use of the communication protocol in the vehicle system and various hardware to establish the wireless connection between road users. By identifying some driver triggered actions which are necessary to alert other drivers and road users within an area, a safety alert message would be broadcast-ed. The message would then be received by other road users so they could be aware of their surroundings. With the use of this safety alert system for road users, they could be more informed about their current surroundings, whenever the safety alert message was received. By doing so, it would help to enhance road safety.